Migration, Transmission, Localisation Visual Art in Singapore (1886-1945) - Yeo, Mang Thong (National Gallery Singapore, 2019)
Drawing mainly on advertisements and comics in Chinese newspapers, Singaporean scholar and educator Yeo Mang Thong demonstrates how Singapore was an important hub for artists who travelled to and lived in Singapore. Yeo's research features amongst other things essays on sojourning artists, and fills a gap in scholarship on the pre-war visual arts scene in Singapore. Originally in Chinese, this English translation aims to bring his research to a broader audience.